DonoSync: A Mobile App for Efficient Donations - Abdulkarim Sani, Mukhtar; Mat Rejab, Mazidah (Applied Information Technology And Computer Science, 2024)
DonoSync addresses the pressing challenge of inefficient donation management by introducing an innovative system. This project endeavors to overhaul donation tracking, ensuring transparent and efficient philanthropic efforts. Employing an iterative software development approach, it emphasizes user-centric features and rigorous phases of planning, analysis, design, and user acceptance testing. Findings showcase DonoSync's potential to significantly enhance donation management across diverse sectors. Discussions center on refining the system for sustained effectiveness, highlighting the need to further explore its implementation nuances and scalability in various philanthropic environments. The study sets the stage for future research aimed at optimizing and expanding DonoSync's impact.